2008
DOI: 10.1590/s0102-695x2008000300005
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic effect of the hydroalcoholic extract of leaves of Averrhoa carambola L. (Oxalidaceae)

Abstract: RESUMO: "Efeito hipoglicemiante do extrato hidroalcoólico de folhas de Averrhoa carambola L. (Oxalidaceae)". O efeito do tratamento via oral (20 mg/kg x day) com extrato hidroalcoólico de folhas de Averrhoa carambola L. (EHFC) sobre a glicemia de jejum (15 h) foi examinada ao compararmos ratos que receberam veículo (Grupo controle) ou EHFC (Grupo EHFC) durante 15 dias. O grupo EHFC apresentou menor glicemia de jejum (p 0,05). Em contraste, o grupo EHFC apresentou maior (p 0,05) produção hepática glicose a part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 17 publications
(17 reference statements)
0
21
0
Order By: Relevance
“…The species A. carambola presents hypoglycemic (Chau et al, 2004a;Ferreira et al, 2008), hypocholesterolemic (Chau et al, 2004b), antimicrobial (Hsu et al, 2007), antioxidant (Shui & Leong, 2006), and anti-infl ammatory (Cabrini et al, 2011) effects. An alcoholic extract of the stems of A. carambola has been shown to exhibit selective activity against brain tumor cells while that of the leaves was effective against liver carcinoma cells (Tadros & Sleem, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The species A. carambola presents hypoglycemic (Chau et al, 2004a;Ferreira et al, 2008), hypocholesterolemic (Chau et al, 2004b), antimicrobial (Hsu et al, 2007), antioxidant (Shui & Leong, 2006), and anti-infl ammatory (Cabrini et al, 2011) effects. An alcoholic extract of the stems of A. carambola has been shown to exhibit selective activity against brain tumor cells while that of the leaves was effective against liver carcinoma cells (Tadros & Sleem, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of Penicillium sp. lectin solution to scavenge hydrogen peroxide radicals was determined as described [44] where Abs A is the absorbance of the control reaction and Abs B is the absorbance of the lectin solution. The half maximal inhibitory concentration (IC 50 ) was determined as described above.…”
Section: Hydrogen Peroxide Radical Scavenging Assaymentioning
confidence: 99%
“…[24] Treatment with hydroalcholic extracts of the leaves resulted in reduction in fasting glycemia, which was not mediated by an inhibition of hepatic gluconeogenesis and / or an increased glucose uptake by muscles. [25] Hydro alcoholic extracts of the leaves also showed anti-ulcer activity, with a different mechanism of action for the anti-ulcerogenic activity. As hydro alcoholic extract contains triterpenes, flavonoids, and mucilage, the partial anti-ulcer activity could be due to their effects.…”
Section: Medicinal Usesmentioning
confidence: 99%
“…[28] It is also possible that these high flavonoid contents may act in a synergistic manner with other A. carambola components to achieve these bioactivities. Ferreira et al [25] reported that the reduction of fasting glycemia promoted by the treatment with hydroalcoholic extracts of the leaves was not mediated by an inhibition of hepatic gluconeogenesis and/or an increased glucose uptake by muscles.…”
Section: Leafmentioning
confidence: 99%